Experimental investigation of the impact of compound‐specific dispersion and electrostatic interactions on transient transport and solute breakthrough. Issue 2 (3rd February 2017) - Muniruzzaman, Muhammad; Rolle, Massimo
Abstract: This study investigates the effects of compound‐specific diffusion/dispersion and electrochemical migration on transient solute transport in saturated porous media. We conducted laboratory bench‐scale experiments, under advection‐dominated regimes (seepage velocity: 0.5, 5, 25 m/d), in a quasi two‐dimensional flow‐through setup using pulse injection of multiple tracers (both uncharged and ionic species). Extensive sampling and measurement of solutes' concentrations (∼1500 samples; >3000 measurements) were performed at the outlet of the flow‐through setup, at high spatial and temporal resolution. The experimental results show that compound‐specific effects and charge‐induced Coulombic interactions are important not only at low velocities and/or for steady state plumes but also for transient transport under high flow velocities. Such effects can lead to a remarkably different behavior of measured breakthrough curves also at very high Péclet numbers. To quantitatively interpret the experimental results, we used four modeling approaches: classical advection‐dispersion equation (ADE), continuous time random walk (CTRW), dual‐domain mass transfer model (DDMT), and a multicomponent ionic dispersion model. The latter is based on the multicomponent formulation of coupled diffusive/dispersive fluxes and was used to describe and explain the electrostatic effects of charged species. Furthermore, we determined experimentally the temporal profiles of the flux‐related dilution index. This metric of mixing, used in connection with the traditional solute breakthrough curves, proved to be useful to correctly distinguish between plume spreading and mixing, particularly for the cases in which the sole analysis of integrated concentration breakthrough curves may lead to erroneous interpretation of plume dilution. Key Points: Investigation of 2‐D transient transport with high‐resolution multitracer and multicomponent ionic flow‐through experiments Distinct breakthrough curves of different conservative solutes in strongly advection‐dominated flows Both spreading and mixing depend on tracer diffusion and charge‐induced Coulombic interactions